Comparative Analysis of Gas Emissions from Ecokiln and Artisanal Brick Kiln During the Artisanal Firing of Bricks - Diaz-Robles, L (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This article focuses on the research of gas emissions in two types of brick kilns located in the Maule Region, Chile. One of them is an artisanal brick kiln known as a “chonchón” (AKC), while the other is a semi-artisanal brick kiln with an improved design. The latter is referred to as the Ecokiln. This study focuses on the assessment of the emission profiles of key pollutants such as particulate matter (PM), CO, CO2, SO2, and NOx. The emission measurements of gasses, temperature, and flow were conducted during the operation of the kilns. These measurements were carried out following the protocol established by Chilean standards. The Ecokiln’s design facilitates optimal fluid dynamics. In direct comparison to the AKC, it exhibits reduced fuel consumption, shorter operation periods, an increased brick processing capacity, decreased burnt brick losses, and notably lower emissions, with a concentration of SO2 that is 83% less than that of the AKC, NOx emissions, 58% lower than the AKC, and a remarkable 74.3% reduction in PM10 emissions. Moreover, the Ecokiln reduces pollutant emissions, improving the well-being of brickmakers and their communities. These results offer insights into the environmental impact of local brick production and support sustainable manufacturing practices. © 2024 by the authors.